Prinsip Pengawasan Hubungan Kerja Di Bidang Pengupahan Dalam Rangka Perlindungan Pekerja/Buruh - Megarani Arsyi Andini (Universitas Muhammadiyah Jember, 2017)
Surveillance the enforcement at the protection of workers in the area of wages in order to ensure the rights and obligations of workers by employers, the results of the review to the future can be used as a material in reorienting legislation exists and realized in the policy formulation in legal reform so that the future is no longer the norm disharmony in efforts to enforce the law, which it will be directly proportional to the effectiveness of law enforcement, especially in the context of supervision in the area of wages laborers / workers. The conclusion of this article are in currently reform needs to be rethought and conducted a review of the minimum wage as one form of wage protection. Determination of wages and periodic wage stage increase in is in need of change. The new concept as an alternative to minimum wage legislation is needed in after reformation period is one of with strengthen supervision in employment particularly in the area of wages